Global Responses of Resistant and Susceptible Sorghum (Sorghum bicolor) to Sugarcane Aphid (Melanaphis sacchari) - Tetreault, Hannah M.; Grover, Sajjan; Scully, Erin D.; Gries, Tammy; Palmer, Nathan A.; Sarath, Gautam; Louis, Joe; Sattler, Scott E. (Frontiers in Plant Science, 2019)
The sugarcane aphid (Melanaphis sacchari) has emerged as a significant pest for sorghum. The use of sugarcane aphid-resistant sorghum germplasm with integrated pest management strategies appears to be an excellent solution to this problem. In this study, a resistant line (RTx2783) and a susceptible line (A/BCK60) were used to characterize the differences in plant responses to the sugarcane aphid through a series of experiments, which examined global sorghum gene expression, aphid feeding behavior and inheritance of aphid resistance. The global transcriptomic responses to sugarcane aphids in resistant and susceptible plants were identified using RNA-seq and compared to the expression profiles of uninfested plants at 5, 10 and 15 days post-infestation. The expression of genes from several functional categories were altered in aphid-infested susceptible plants, which included genes related to cell wall modification, photosynthesis and phytohormone biosynthesis. In the resistant line, only 31 genes were differentially expressed in the infested plants relative to uninfested plants over the same timecourse. However, network analysis of these transcriptomes identified a co-expression module where the expression of multiple sugar and starch associated genes were repressed in infested resistant plants at 5 days and 10 days. Several nucleotide-binding-site, leucine-rich repeat (NBS-LRR) and disease resistance genes similar to aphid resistance genes identified in other plants are identified in the current study which may be involved in sugarcane aphid resistance. The electrical penetration graph (EPG) results indicated that sugarcane aphid spent approximately twice as long in non-probing phase, and approximately a quarter of time in phloem ingestion phase on the resistant and F1 plants compared to susceptible plant. Additionally, network analysis identified a phloem protein 2 gene expressed in both susceptible and resistant plants early (day 5) of infestation, which may contribute to defense against aphid feeding within sieve elements. The resistant line RTx2783 displayed both antixenosis and antibiosis modes of resistance based on EPG and choice bioassays between susceptible, resistant and F1 plants. Aphid resistance from RTx2783 segregated as a single dominant locus in the F2 generation, which will enable breeders to rapidly develop sugarcane aphid-resistant hybrids using RTx2783 as the male parent.